Physiological Basics of Forming Movement Skills and Teaching Sports Techniques (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In this article, a complex process is carried out in the Jude during the formation and control of movements, in the human central nervous system and nervous system. This is the case when, in sports, several muscles in my arganizim and cases associated with nerve ischemia are reflected in the control of dynamic movements and keeping certain states of the torso in balance.